The dismantling of Japan's empire in East Asia deimperialization, postwar legitimation and imperial afterlife - Muminov, Sherzod; Kushner, Barak 1968- (London New York Routledge, Taylor & Francis Group, 2017)
"The end of Japan's empire appeared to happen very suddenly, and cleanly--but, as this book shows, it was in fact very messy, with a long period of establishing or re-establishing the postwar order. Moreover, as the authors argue, empires have afterlives, which, in the case of Japan's empire, is not much studied. This book considers the details of de-imperialization, including repatriation of Japanese personnel, the redrawing of boundaries, issues to do with prisoners of war and war criminals, new arrangements for democratic political institutions, for media and for the regulation of trade. It also discusses the continuing impact of empire: on the countries ruled or occupied by Japan, where as a result of Japanese management and administration, both formal and informal, patterns of behavior and attitudes were established which continued subsequently. This was true in Japan itself, where returning imperial personnel had to be absorbed and adjustments made to imperial thinking; and on present day East Asia, where the shadow of Japan's empire still lingers. This legacy of unresolved issues concerning the correct relationship of Japan, an important, energetic, outgoing nation and a potential regional 'hub,' with the rest of the region not comfortably settled in this era, remains a fulcrum of regional dispute"--Provided by publisher.
Introduction: Angles of empire -- Section One. The new postwar order : meaning and significance -- Kato Kiyofumi - The decline of the Japanese Empire and the transformation of the regional order in East Asia -- Kawashima Shin - "De-imperialization" in early postwar japan : adjusting and transforming institutions of empire -- Barak Kushner - Imperial loss and Japan's search for postwar legitimacy -- Araragi Shinzo - Collapse of the Japanese empire and the great migrations : repatriation, assimilation, and remaining behind -- Section Two. War criminals, POWs, and the imperial breakdown -- Sandra Wilson - The shifting politics of guilt : the campaign for the release of Japanese war criminals -- Sarah Kovner - Allied POWs in Korea : life and death during the Pacific War -- Franziska Seraphim - Carceral geographies of Japan's vanishing empire : war criminals' prisons in Asia -- Sherzod Muminov - Prejudice, punishment and propaganda : post-imperial Japan and the Soviet versions of history and justice in East Asia, 1945-1956 -- Section Three. Diplomacy, law, and the end of empire -- Matthias Zachmann - Sublimating the empire : how Japanese experts of international law translated "Greater East Asia" into the postwar period -- Kanda Yutaka - The transformation of a Manchukuo imperial bureaucrat to postwar supporter of the Yoshida Doctrine : the case of Shiina Etsusaburo -- Park Jung Jin - North Korean nation building and Japanese imperialism : people's nation, "people's diplomacy" and the Japanese technicians -- Erik Esselstrom - Humanitarian hero or communist stooge? : the ambivalent Japanese reception of Li Dequan in 1954 -- Section Four. Media and the imperial aftermath -- Sato Takumi - The "pacifist" magazine Sekai : a barometer of postwar thought -- Shirato Kenichiro - Post-imperial broadcasting networks in China and Manchuria -- Michael Baskett - Parting the Bamboo Curtain : Japanese Cold War film exchange with China -- Comparative epilogue / Kerstin von Lingen - Germany as a role model? : coming to terms with Nazi war deeds, 1945-2015.
Includes bibliographical references and index.
Keywords: World War, 1939-1945 -- Influence; Imperialism -- History -- 20th century; Decolonization -- East Asia -- History -- 20th century; Postcolonialism -- East Asia -- History -- 20th century; East Asia -- Politics and government -- 1945-.; East Asia -- Relations -- Japan; Japan -- Foreign relations -- 1945-1989.; Japan -- Relations -- East Asia